2013
DOI: 10.3109/03009742.2013.771211
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic arthritis mutilans (PAM) in the Nordic countries: demographics and disease status. The Nordic PAM study

Abstract: PAM in the Nordic countries has a low prevalence, with only three to five cases per million inhabitants. The majority of the patients present with mild skin disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 14 publications
2
23
0
1
Order By: Relevance
“…We have previously reported inclusion and exclusion criteria for the Nordic PAM Study, as well as demographics and disease settings in 59 patients with PAM (14). The objectives of the present study are to report the quality of life of PAM sufferers in the Nordic countries, and to describe effects of the disease on functional capacity and social life.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported inclusion and exclusion criteria for the Nordic PAM Study, as well as demographics and disease settings in 59 patients with PAM (14). The objectives of the present study are to report the quality of life of PAM sufferers in the Nordic countries, and to describe effects of the disease on functional capacity and social life.…”
Section: Methodsmentioning
confidence: 99%
“…In an early Swedish PsA cohort (n = 334) with a 10 year follow-up, none of the patients developed PAM (16, personal communication T Husmark, 2014). In our recent epidemiological study in the Nordic population, the prevalence of PAM was found to be only 3.9 per million inhabitants (14). Occasionally, arthritis mutilans can also be associated with other severe arthritic diseases, e.g.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Only studies in which clinical data of patients with AM were specifically reported were extracted. Full articles of all relevant studies were retrieved, and manual searches of reference lists from these articles were performed, identifying 14 suitable studies ( Figure 2) 3,4,5,6,7,8,9,10,11,12,13,14,15,16 . Including our series, a total of 120 patients with AM are described ( Table 1).…”
Section: Casementioning
confidence: 99%
“…Данные о превалировании мужчин среди больных ПсА подтверждают результаты исследова-ния испанской популяции (среди больных ПсА мужчин 57,2%, женщин -43,8%) и популяции пе-руанских островов (65%) [25,26]. Среди европеоид-ных популяций (норвежской, исландской) распро-страненность ПсА у женщин и мужчин одинакова [27].…”
unclassified